ANALYSIS OF RELAPSE RATE AND METASTASES OF HIGH DIFFERENTIATED THYROID CANCER - E. V. Savenok; E. S. Minakova; O. V. Ryzhikh; E. D. Panov; E. A. Karapetyan (Опухоли головы и шеи)
Analysis of rate of relapses and metastases with well-differentiated thyroid cancer was performed for patients in 2009 to 2013. The study involved 189 patients with thyroid cancer including 98 (51.9 %) patients suffering from papillary thyroid cancer, 77 (40.7 %) patients suffering from follicular thyroid cancer, and 14 (7.4 %) patients suffering from medullary thyroid cancer. 2.04 % of the 98 patients suffering from papillary thyroid cancer manifested a relapse, and lymphogenic metastases of cancer were revealed with 1.0 % of patients. With follicular thyroid cancer (n = 77), lymphogenic metastases were registered in 7.8 % of cases, relapses were revealed in 1.3 % of cases. This analysis demonstrated that observation of patients for 5 years revealed a higher percentage of metastases with patients that suffered from follicular thyroid cancer.